Identification of adenovirus genes that require template replication for expression. - Crossland, L D (1983)
The relationship between adenovirus type 2 DNA replication and expression of intermediate stage viral genes was investigated. The 1.03-kilobase mRNA from early region 1b (E1b) and the mRNAs coding for proteins IX and IVa2 were first detected between 6 and 8 h postinfection. Inhibition of viral DNA replication with hydroxyurea prevented expression of the IX and IVa2 mRNAs, but not of the E1b mRNA. Pulse-labeling experiments demonstrated that the block of IX and IVa2 expression in hydroxyurea-treated cells was at the level of transcription. By a series of superinfection experiments, it was determined that the viral and cellular factors present during the late stage of adenovirus infection are insufficient to activate IX gene expression. The viral DNA template must first replicate before IX transcription can begin.